Hospital re‐admission after critical care survival: a systematic review and meta‐analysis. (29th December 2021) - McPeake, J.; Bateson, M.; Christie, F.; Robinson, C.; Cannon, P.; Mikkelsen, M.; Iwashyna, T. J.; Leyland, A. H.; Shaw, M.; Quasim, T.
Summary: Survivors of critical illness frequently require increased healthcare resources after hospital discharge. We undertook a systematic review and meta‐analysis to assess hospital re‐admission rates following critical care admission and to explore potential re‐admission risk factors. We searched the MEDLINE, Embase and CINAHL databases on 05 March 2020. Our search strategy incorporated controlled vocabulary and text words for hospital re‐admission and critical illness, limited to the English language. Two reviewers independently applied eligibility criteria and assessed quality using the Newcastle Ottawa Score checklist and extracted data. The primary outcome was acute hospital re‐admission in the year after critical care discharge. Of the 8851 studies screened, 87 met inclusion criteria and 41 were used within the meta‐analysis. The analysis incorporated data from 3, 897, 597 patients and 741, 664 re‐admission episodes. Pooled estimates for hospital re‐admission after critical illness were 16.9% (95%CI: 13.3–21.2%) at 30 days; 31.0% (95%CI: 24.3–38.6%) at 90 days; 29.6% (95%CI: 24.5–35.2%) at six months; and 53.3% (95%CI: 44.4–62.0%) at 12 months. Significant heterogeneity was observed across included studies. Three risk factors were associated with excess acute care rehospitalisation one year after discharge: the presence of comorbidities; events during initial hospitalisation (e.g. the presence of delirium and duration of mechanical ventilation); and subsequent infection after hospital discharge. Hospital re‐admission is common in survivors of critical illness. Careful attention to the management of pre‐existing comorbidities during transitions of care may help reduce healthcare utilisation after critical care discharge. Future research should determine if targeted interventions for at‐risk critical care survivors can reduce the risk of subsequent rehospitalisation.